Strategi Efektif Memperkuat Hubungan Remaja Kristen dengan Tuhan Melalui Media Sosial di Era Digital (International Forum of Researchers and Lecturers, 2024)
Christian teenagers represent a young generation with great potential and hope as the successors of the church. In the rapidly evolving digital era, Christian teenagers often do not use social media wisely. Many of them use social media as a platform to express hatred, insults, and spread false news. This research aims to formulate effective strategies that can help Christian teenagers strengthen their faith in God through social media. The research method used is qualitative, by collecting various references from journal articles, books, and other internet sources. Christian teenagers have the opportunity to listen to God's word through live broadcasts or videos on platforms such as TikTok, Instagram, Facebook, and other applications. Additionally, they can build positive online communities and be good role models in the virtual world. Thus, Christian teenagers can strengthen their relationship with God through the proper use of social media.